One pot synthesis of 1-((1-aryl-1H-1,2,3-triazol-4-yl)methyl)-1H-benzo[d] imidazoles in ionic liquids: Evaluation of antioxidant and antimicrobial activities - Seeka, Suresh; Narsimha, Sirassu; Battula, Kumaraswamy; Shaikh, Althaf Hussain; Tangeda, Savitha Jyostna; Nagavelli, Vasudeva Reddy (European Journal of Chemistry, 2015)
In view of pharmacological importance of benzimidazole and 1,2,3-triazole nuclei, we made an effort to synthesize the bi-functional mimic 1,2,3-triazolyl-benzimidazoles through the copper catalyzed azide-alkyne 1,3-dipolar cycloaddition reaction in ionic liquids. The synthesized compounds were characterized by NMR, IR and Mass spectral analysis. The synthesized compounds were screened for antimicrobial and antioxidant activities. A good number of the compounds found to possess potent antioxidant and antimicrobial activities.